Perceptions of prospective specialists and non-specialists towards technical terms in marketing - Ismail, Yusof; Ahamed Shah, Mohamed Ismail (2010)
Technical terms are an integral part of a discipline. They enrich and help distinguish among disciplines. The irony is that even among specialists some technical terms are incomprehensible; the terms impede, instead of expedite, the communication process. Some technical terms fail to satisfy the basic needs of communication such as message clarity. The present study aims to identify and verify a select list of twenty two technical terms which may be considered fundamental or basic in the discipline of Marketing. The study creates an instrument to help collect input from prospective specialists and non-specialists of Marketing towards their perception of, and decision on, the need to have common understanding of technical Marketing terms. A questionnaire was administered on 82 non-specialists and 26 specialist undergraduate students of a public university whose medium of instruction is English. Results show that the respondents moderately agree that they will lose if they lack knowledge of the marketing technical terms. They also believed that using correct terms expedites the communication process. A statistical analysis called Cronbach alpa (.863) confirms the significantly high degree of inter-relatedness among the twenty two Marketing terms tested in the study. Another statistical technique called an exploratory factor analysis procedure was used to statistically group the specified list of technical terms. The procedure produced five categories of technical terms that were labelled as providers of products, distributors, sales, pricing, and product. The last four categories represent the universally recognized four P‟s of marketing: place, promotion, pricing, and product. The study confirmed at least twenty two technical terms that help producers, marketers and consumers communicate effectively.